2002
DOI: 10.1097/00001888-200210000-00013
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Pediatrics Residentsʼ Mathematical Skills for Prescribing Medication

Abstract: Pediatrics residents need to receive additional education in performing the calculations needed to prescribe medications. In addition, residents should be required to demonstrate these necessary mathematical skills before they are allowed to prescribe medications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
38
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(40 citation statements)
references
References 9 publications
1
38
1
Order By: Relevance
“…It did, however, involve a conversion from micrograms to milligrams so it seems likely that the problem was one of arithmetic. The potential for ten-fold errors (or worse) under these circumstances has already been widely reported [9][10][11][12].…”
mentioning
confidence: 88%
“…It did, however, involve a conversion from micrograms to milligrams so it seems likely that the problem was one of arithmetic. The potential for ten-fold errors (or worse) under these circumstances has already been widely reported [9][10][11][12].…”
mentioning
confidence: 88%
“…Six of nine doctors with no paediatric experience answered all questions correctly compared to only four of 23 with previous paediatric experience. Other studies have suggested that clinical experience has little to do with making calculation errors, but that the necessary skills for calculations are obtained earlier in education 8 9. A national competency based assessment in prescribing for children/neonates has been recommended, which could be embedded within the postgraduate MRCPCH exam 7.…”
Section: Medical School Teaching Of Prescribing and Therapeuticsmentioning
confidence: 99%
“…15 Evidence in the literature confirms that some pediatric health care practitioners have difficulty calculating an appropriate medication dose, and studies recommend that practitioners should be trained in dosing calculation and demonstrate sufficient competency with observation. [20][21][22] The impact of an antibiotic standard dosing table was significant in the emergency department setting. Many of our clinicians in the emergency department were not familiar with appropriate pediatric dose calculation as they are not pediatricians by training.…”
Section: Discussionmentioning
confidence: 99%
“…Another source for dosing errors in children is misplacement of the decimal point after calculating the dose. 4,8,9 Antibiotics and sedatives are the medications most widely prescribed in the pediatric population and are the drug classes most commonly reported involved in pediatric medication errors. 6,7,10,11 Subtherapeutic dosing of antibiotics has been identified as a frequent problem in the pediatric population as many clinicians do not consider weight when they calculate the dose or they simply calculate the pediatric dose as one half of the adult dosing.…”
Section: Introductionmentioning
confidence: 99%